COMPARATIVE CHARACTERISTICS OF THE QUALITY OF LIFE OF KHANTY-MANSI AUTONOMOUS REGION AND TATARSTAN REPUBLIC - L. A. Valiullina; I. I. Antonova; K. A. Tazetdinova (Russian Journal of Economics and Law)
The article gives comparative characteristics of the quality of life of the population of Khanty-Mansi autonomous region and Tatarstan Republic basing on the population quality of life index. The compared regions› social problems are compared. The data are presented characterizing 10 Russian regions by the quality of life index.